Fraseologiske enheders indplacering i Jysk Ordbog - Arboe, Torben (Nordiske Studier i Leksikografi, 2007)
The topic is presented within a framework of relevant overview schemata in Lüger 1999 and on the basis of especially the latest published parts of the Jutlandic Dictionary (www.jyskordbog.dk), from HA- to HU-. Comments are made as to the terminological discussion of e.g. “phraseologisms”, “phrasemes”: they may be used as terms not only for units below sentence-level, but also for idioms with sentence-structure (cf. chapters 2–3). Particular attention is drawn to “one-word-phrasemes” (juxtapositions, chap. 2.3), and to “phraseme-lemmas”, i.e. lemmas created just to account for a special phraseme (chap. 4). Concludingly, the microstructures of very large articles (nouns and verbs) are inspected as to the precise placing of the large amount of set phrases (chap. 5).